Critical Library Performativity: Toward Progressive Change in Academic Library Management and Organizations - Leebaw, Danya (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2020)
Can library managers be #critlib? Do articles and conversations about critical theory really lead to progressive changes in library organizations and management? Critical management studies (CMS), a subfield of management studies, calls for denaturalization of taken-for-granted management practices, reflexivity in methods, and anti-performative goals. However, worried that CMS is too idealistic and ineffective, some of its adherents have proposed a theoretical construct they call “critical performativity” (CP). CP aims to bridge critical theory and authentic engagement with practicing managers. This article introduces and summarizes CP scholarship, and then considers the lessons CP has for critical library scholars, workers, and managers. Unlike our CMS scholarly counterparts, most librarians who align with critical perspectives are also themselves practitioners. For us, CP offers useful framing and thought-provoking ideas for integrating our critical leanings and our daily practice in order to work for achievable change.